2019
DOI: 10.3389/fphys.2019.00769
|View full text |Cite
|
Sign up to set email alerts
|

On the Shape of the Force-Velocity Relationship in Skeletal Muscles: The Linear, the Hyperbolic, and the Double-Hyperbolic

Abstract: The shape of the force-velocity (F-V) relationship has important implications for different aspects of muscle physiology, such as muscle efficiency and fatigue, the understanding of the pathophysiology of several myopathies or the mechanisms of muscle contraction per se , and may be of relevance for other fields, such as the development of robotics and prosthetic applications featuring natural muscle-like properties. However, different opinions regarding the shape of the F-V relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 229 publications
(474 reference statements)
3
92
0
2
Order By: Relevance
“…A possible explanation for the decrease in plantarflexor moment without an accompanying decrease in plantarflexion muscle activity may be that the plantarflexors were operating at a less effective point of the forcelength relationship at reduced gravity levels. Maximum muscle force is dependent on both the muscle length and velocity of the contraction [49,56,57]. If gravity level influenced the length and speed of muscle contraction, then electromyography values may not change even though the resultant muscle force may be different.…”
Section: Plos Onementioning
confidence: 99%
“…A possible explanation for the decrease in plantarflexor moment without an accompanying decrease in plantarflexion muscle activity may be that the plantarflexors were operating at a less effective point of the forcelength relationship at reduced gravity levels. Maximum muscle force is dependent on both the muscle length and velocity of the contraction [49,56,57]. If gravity level influenced the length and speed of muscle contraction, then electromyography values may not change even though the resultant muscle force may be different.…”
Section: Plos Onementioning
confidence: 99%
“…In multi-joint movements, the FV-relationship is commonly described as linear [ 8 ], in contrast to the hyperbolic relationship observed in isolated muscles or single-joint movements [ 7 ]. In practice, athletes can perform maximal efforts against different loads while force and velocity are measured during vertical jumping or similar multi-joint movements.…”
Section: Introductionmentioning
confidence: 99%
“…Hill's equation has been considered a reference equation in different muscle preparations and during in situ conditions in humans. However, several studies found deviations from Hill's hyperbolic function in the high-force/low-velocity region of the F-V relationship (6).…”
Section: Introductionmentioning
confidence: 99%